An Audit into the Nature of Operations of Agro-processing Micro, Small and Medium Enterprises (MSMEs) in Uganda - Kigozi, Julia; Baidhe, Emmanuel; Mukisa, Ivan Muzira; Muyanja, Charles; Namubiru, Leatitiah; Katarikawe, Brenda (Journal of Food Industry, 2024)
The agro-processing Micro, Small, and Medium-Sized Enterprises (MSMEs) form an integral part of the manufacturing sector in Uganda. To effectively facilitate product certification among MSMEs, there is a need to fully understand the nature of their operations so that appropriate interventions can be put in place. This study assessed the status quo of operations at selected MSMEs in Uganda. A semi-structured paper-based questionnaire was administered to the owners, managers, or supervisors of 40 selected agro-processing MSMEs enrolled under the project “Empowerment of the Agro-Processing Industry to meet the Quantity and Quality Standards for the Local and Export Market”, a programme enhancing the practical skills of students at Makerere University dubbed the “EAPI Project.” The seven-section questionnaire consisted of both quantitative and qualitative questions focusing on (i) product optimization, (ii) raw material verification and storage, (iii) good manufacturing practices, (iv) measuring and testing equipment, (v) product assessment, presentation, and storage, (vi) waste and pest management, and (vii) infrastructure and energy utilization. The results indicated that only 23.7% of agro-processing MSMEs clearly understood the standards. Packaging was the most optimized parameter (74.4%), followed by texture and sensory properties (59% and 51.1%, respectively). About 74% of the agro-processing MSMEs were compliant in declaring the raw materials on the product label. Maintenance of valid medical certificates, routine inspection of personnel, and provision of protective gear ranked low, with a score of 1 out of 10. Inadequate documentation was a cross-cutting issue for all operations, yet it was a driver for GMPs. There is a need to strengthen the understanding and practice of food processing standards from the Uganda National Bureau of Standards (UNBS), in the agro-processing MSMEs through continuous human and institutional-capacity development programs.